Lobular capillary hemangioma of the trachea – A rare cause of stridor in elderly: A case report with review of literature. (June 2021) - Maturu, Venkata Nagarjuna; Vaddepally, Chetan Rao; Narahari, Narendra Kumar; Pulikanti, Bhulaxmi; Sethi, Shweta
Lobular capillary hemangioma is a rare benign lesion found within the tracheobronchial tree. Patients usually present with recurrent hemoptysis, chronic cough, and rarely, with airway obstruction. We present a case of tracheal lobular capillary hemangioma in a 70-year-old man who presented with stridor and chronic cough. Bronchoscopy showed a 2-cm polypoidal lesion below the vocal cords, which was resected with an electrocautery snare using a rigid bronchoscope. Clinicians should be aware of this entity as one of the differentials for stridor. Bronchoscopic excision of the tumor is feasible and is a minimally invasive therapeutic option for management of these tumors.